DAMPAK KRISIS EKONOMI TERHADAP KINERJA SEKTOR INDUSTRI: PENDEKATAN MODEL KESEIMBANGAN UMUM TERAPAN INDORANI - Y. Sri Susilo; Budiono Sri Handoko (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
This paper tries to examine the impact of economic crisis on industry performance during 1997 - 1998. The performance was measured in terms of value added, employment, domestic prices, and exports volume. The method used in this research was simulation with INDORANI Computable General Equilibrium Model (CGE Model). The results of the simulation were then crosschecked with the data provided by BPS, field survey, and others preliminary research.The results of this research show that in general, the economic crisis has a negative impact on industry performance. The negative impact consists of the increasing domestic prices, decreasing value added and export volume, lower production for domestic market, and lower rate of employment. Howewer, domestic resources-based and/or export oriented industries (such as food and beverages, plywoods, chemicals and non-ferrous industries) have better negative impacts compared to import resource-based and domestic-oriented industries (such as iron and steel, and machinery industries).Keywords: economic crisis, industry performance, INDORANI CGE-Model.